2019
DOI: 10.2109/jcersj2.19041
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature deposition of Li substituted (K,Na)NbO<sub>3</sub> films by a hydrothermal method and their structural and ferroelectric properties

Abstract: Li substituted (K,Na)NbO 3 films with K-rich composition against polymorphic phase boundary were deposited at 240°C on (100)La:SrTiO 3 substrates by hydrothermal method. The amount of Li content in films was controlled by changing the nominal composition of raw materials, A = [LiOH]/([KOH] + [NaOH] + [LiOH]). X-ray diffraction measurement showed that {001} c-oriented epitaxial (K,Na,Li)NbO 3 films were obtained for all nominal compositions (A = 00.1). However, the diffraction peaks originated from a secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Mixed tantalate-niobates have also been prepared using hydrothermal approaches. [158] Other substitutions in the this family of perovskites include lithium, in (Na,K)NbO3-LiTaO3 thin films, [159] and also epitaxial (K,Na,Li)NbO3 films which were grown hydrothermally on (100)-La:SrTiO3 substrates to give layers that showed ferroelectric hysteresis loops, [160] and sulfur-containing NaTaO3 produced directly by use of Na2S2O3•5H2O as a hydrothermal reagent. [161] Other niobates whose hydrothermal synthesis has been studied include AgNbO3, whose photocatalytic properties have been studied, [162] and Pb(Mg1/3Nb2/3O3), which was formed at high KOH concentrations in preference to a pyrochlore phase.…”
Section: Niobates and Tantalatesmentioning
confidence: 99%
“…Mixed tantalate-niobates have also been prepared using hydrothermal approaches. [158] Other substitutions in the this family of perovskites include lithium, in (Na,K)NbO3-LiTaO3 thin films, [159] and also epitaxial (K,Na,Li)NbO3 films which were grown hydrothermally on (100)-La:SrTiO3 substrates to give layers that showed ferroelectric hysteresis loops, [160] and sulfur-containing NaTaO3 produced directly by use of Na2S2O3•5H2O as a hydrothermal reagent. [161] Other niobates whose hydrothermal synthesis has been studied include AgNbO3, whose photocatalytic properties have been studied, [162] and Pb(Mg1/3Nb2/3O3), which was formed at high KOH concentrations in preference to a pyrochlore phase.…”
Section: Niobates and Tantalatesmentioning
confidence: 99%
“…But, this does not occur on polymer (or amorphous) ones, where seed (nucleation) layers have to be previously deposited on the surface of the substrate. [39][40][41][42][43][44][45][46] To the knowledge of the authors, only Shiraishi et al have reported the Hydrothermal preparation of KNbO 3 (KNN) ferroelectric thin films on flexible polysulfone substrates with a remanent polarization of P R 4.2 µC cm -2 . [39] In this work, a LaNiO 3 perovskite seed layer is deposited by RF-magnetron sputtering on the electroded substrate (Pt/Ti/polysulfone), before the growing of the ferroelectric perovskite.…”
Section: Introductionmentioning
confidence: 99%
“…1). [11,12,14,39,40,44,46, Fukushima et al, [74] and Budd et al, [75,76] were among the first that demonstrated the successful fabrication of ferroelectric oxide thin films (PbTiO 3 , Pb(Zr,Ti)O 3 , PZT and 2014 [39] 2010 [46] 2019 [40] 2017 [44] 2017 [73] 2015 [72] 2014 [11] 2020 [71] 2011 [63][64][65] 2014 [62] 2008 [68] 2010 [67] 1999 [61] 2020 [70] 2003 [69] 2004 [12] 2000 [66] 2014 [62] 2016 [58] 2008 [57] 2017 [56] 2008 [14] 2001 [60] 2013 [59] 2018 [52] 2003 [53] 2000 [54] 2009 [55] The graphic shows the ferroelectric composition of the film, the processing temperature at which they were processed and the ferroelectric remanent polarization (PR) measured in them. The CSD strategy/ies used for the low-temperature solution processing of the films are also shown.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, hydrothermal method is a low temperature deposition technique, with which one can deposit (K,Na)NbO 3 -based films. [16][17][18][19][20][21][22][23] This method is a simple wet process using alkaline source solutions and oxide powders with process temperatures below 300 °C, which is much lower than those of other deposition methods. In our previous study, it was found that K-rich (K x Na 1−x )NbO 3 films (x = 0.8-0.9) deposited by the hydrothermal method exhibited physical and electrical characteristics suitable for applications to various piezoelectric devices.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Handoko et al reported the hydrothermal synthesis of (K,Na)NbO 3 -LiTaO 3 films. 26) However, there are a few reports on the hydrothermally-deposited (K,Na)NbO 3 -based films, 22) and the effect of elemental substitution on the physical and electrical properties of these films is unclear.…”
Section: Introductionmentioning
confidence: 99%